2022
DOI: 10.1111/cas.15587
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐induced CXC chemokine ligand 14 expression drives protumorigenic effects through activation of insulin‐like growth factor‐1 receptor signaling in glioblastoma

Abstract: Hypoxic tumor microenvironment (HTM) promotes a more aggressive and malignant state in glioblastoma. However, little is known about the role and mechanism of CXC chemokine ligand 14 (CXCL14) in HTM‐mediated glioblastoma progression. In this study, we report that CXCL14 expression correlated with poor outcomes, tumor grade, and hypoxia‐inducible factor (HIF) expression in patients with glioblastoma. CXCL14 was upregulated in tumor cells within the hypoxic areas of glioblastoma. Hypoxia induced HIF‐dependent exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The GBM8401 cells were maintained in RPMI 1640 (Invitrogen) supplemented with 10% FBS, 10 mM HEPES, and 1% P/S. Primary glioblastoma cells, GBM04T and GBM09T, derived from our previous study [ 22 ], were propagated as tumor spheres in serum-free DMEM-F12 supplemented with 2% B27, 20 ng/mL bFGF, and 20 ng/mL EGF. The human umbilical vein endothelial cells (HUVECs) were procured from Sciencell Company and cultured with endothelial cell medium (ECM) (Sigma-Aldrich) containing 5% FBS, 1% endothelial cell growth supplement (ECGS), and 1% P/S.…”
Section: Methodsmentioning
confidence: 99%
“…The GBM8401 cells were maintained in RPMI 1640 (Invitrogen) supplemented with 10% FBS, 10 mM HEPES, and 1% P/S. Primary glioblastoma cells, GBM04T and GBM09T, derived from our previous study [ 22 ], were propagated as tumor spheres in serum-free DMEM-F12 supplemented with 2% B27, 20 ng/mL bFGF, and 20 ng/mL EGF. The human umbilical vein endothelial cells (HUVECs) were procured from Sciencell Company and cultured with endothelial cell medium (ECM) (Sigma-Aldrich) containing 5% FBS, 1% endothelial cell growth supplement (ECGS), and 1% P/S.…”
Section: Methodsmentioning
confidence: 99%
“…High levels of CXCL14 expression are correlated with overall patient survival in colorectal, breast, endometrial, intraepithelial, and head and neck cancers [30] and suppress tumor progression [31][32][33][34][35]. In contrast, other studies have shown protumor effects of CXCL14 in nasopharyngeal carcinoma, prostate cancer, glioblastoma, non-small-cell lung cancer, and microsatellite-stable colorectal tumors [25,[36][37][38][39].…”
Section: Cxcl14 and Cancermentioning
confidence: 99%
“…Its previous name is breast- and kidney-expressed chemokine (BRAK). The receptor for CXCL14 is not well defined, but it seems that CXCL14 can activate CXCR4, ACKR2 [ 101 ], IGF-1R [ 102 ], and GPR85 [ 103 ]. CXCL14 can also bind to CXCR4 [ 104 ].…”
Section: Cxcl14mentioning
confidence: 99%